2018
DOI: 10.1007/s13224-018-1115-7
|View full text |Cite
|
Sign up to set email alerts
|

Audit of Female Genital Aesthetic Surgery: Changing Trends in India

Abstract: FGCS is no doubt in its infancy in India. However, there is a steady rise in the awareness and demand for these procedures. A combination of procedures to improve individual components leads to improved aesthetic and functional aspects of female genitalia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Information about these conditions and their treatment are more readily available, increasing the demand for these procedures. In a study from India, demand for esthetic vaginal procedure has risen to 28.92% in 2015 from 3.9% in 2012 [16]. In a review of vaginal tightening procedures performed between 2014 and 2019 in Canada, Austin et al reported that posterior vaginoplasty resulted in a high patient satisfaction without complications [17].…”
Section: Discussionmentioning
confidence: 99%
“…Information about these conditions and their treatment are more readily available, increasing the demand for these procedures. In a study from India, demand for esthetic vaginal procedure has risen to 28.92% in 2015 from 3.9% in 2012 [16]. In a review of vaginal tightening procedures performed between 2014 and 2019 in Canada, Austin et al reported that posterior vaginoplasty resulted in a high patient satisfaction without complications [17].…”
Section: Discussionmentioning
confidence: 99%
“…Being non‐invasive, easier to perform and due to lesser downtime energy‐based devices have gained lot of popularity among the physicians and patients. A study conducted in India showed a rising trend in the demand of aesthetic vaginal procedures from 3.9% in 2012 to 28.97% in 2015 2 …”
Section: Psychological Impactmentioning
confidence: 99%
“…Aside from surgery, the advent of nonsurgical methods and energy sources for these indications is receiving tremendous response and patient acceptance ( Karcher and Sadick, 2016 ). The American Society of Plastic Surgeons reported a 30% increase in the rate of vaginal rejuvenation procedures between 2005 and 2006 ( Lowenstein et al, 2014 ), and an Indian study also showed growing trends in the demand of esthetic vaginal procedures from 3.9% in 2012 to 28.97% in 2015 ( Desai and Dixit, 2018 ).…”
Section: Global Awareness and Changing Trendsmentioning
confidence: 99%
“…Dyspareunia and low lubrication were reported as side effects. A recent study of 39 patients undergoing surgical vaginal tightening showed improvements in FSFI from 19.5 to 27 ( Desai and Dixit, 2018 ). This study also showed that 81.6% of patients were very satisfied, 14.5% satisfied, and 3.9% not satisfied with the FCGS procedures.…”
Section: Surgical Vaginoplastymentioning
confidence: 99%